Odpowiedzi

2009-12-25T22:28:47+01:00
Rozwiąz algebraicznie 2x^-y=0
y-x=6
^ tzn do kwadratu

2x²-y=0
y=x+6

2x²-x-6=0
Δ=1+48=49
√Δ=7
x₁=2 lub x₂=-6/4=-3/2=-1,5
y₁=8 lub y₂=4,5

( 2,8 )
( -1,5; 4,5)
2 4 2
2009-12-25T22:40:47+01:00
2x²-y=0
y-x=6

2x²-y=0
x=y-6

2*(y-6)²-y=0
x=y-6

2*(y²-12y+36)-y = 0
x=y-6

2y²-24y+72-y = 0
x=y-6

2y²-25y+72 = 0
a=2 b=-25 c=72
Δ=b²-4ac
Δ=(-25)²-4*2*72
Δ=625-576
Δ=49
√Δ=7
y₁=(-b-√Δ)/2a
y₁=(25-7)/4
y₁=4,5
y₂=(-b+√Δ)/2a
y₂=(25+7)/4
y₂=8

x₁=4,5-6
x₁=-1,5
x₂=8-6
x₂=2

Możliwe pary rozwiązań to 4,5 i -1,5 oraz 8 i 2